CONSIDERAŢII PRIVIND MANAGEMENTUL CALITĂŢII RESURSELOR UMANE - USM ADMIN (Moldova State University, 2008)
In this article there are described and analyzed the trends of the management of quality of human resources what play an important role, in the increase of human performances in view of tasks fulfillment of institution and the needs satis- faction of aspirations of the individuals.